Pengaruh Quality of Work Life dan Motivasi Terhadap Kinerja Pegawai Bank Negara Indonesia Kantor Cabang Malang - Putri, Berlian Melenia; Nurhidayah, Nurhidayah; Primanto, Alfian Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
AbstractÂ This research aims to analyze the influence of Quality of Work Life (QWL) and motivation on employee performance at Bank BNI Malang Branch Office. The number of samples used was 32 employees as respondents. The data collection technique uses a questionnaire, the research method used is quantitative with a multiple linear regression analysis approach. The results of this research show that the variables Qualiy of Work Life (QWL) and motivation simultaneously have a significant effect on employee performance at Bank BNI Malang Branch Office. In addition, motivation is proven to be a significant mediator between employee performance and QWL. The practical implication of these findings is the importance of increasing employee motivation to improve their performance and quality of work life, which in turn will support the achievement of overall organizational goals. This research contributes to understanding the complex dynamics between psychological factors and the work environment in the context of employee productivity and job satisfaction.Â Keywords: Employee performance, motivation and quality of work life (QWL)Â